Aspectos geológicos-geomorfológicos e os parâmetros morfométricos da rede de drenagem: uma análise e discussão sobre um sistema cárstico - Rafael Brugnolli Medeiros; Charlei Aparecido da Silva (Confins)
Evaluating the drainage network morphometry brings with it countless data (channel distribution, drainage density, basin shape, among others) that contribute to subsidize an adequate planning of the hydric resources and, consequently, of the hydrographic basins. This analysis started from a main problem, the fact the Formoso River Hydrographic Basin, Bonito/MS, presents two distinct systems: the karstic and terrigenous systems. These facts made it possible to evaluate their differentiation and how this is reflected in the drainage channels of the basin in question, thus defining the objective of this study. To this end, we used references linking the morphometric analysis to the areal and linear issues of the drainages, in addition to the evaluation of the main components of the landscape, in the role of rocks and relief. The results found brought an important variation among the systems, the predominantly karstic sub-basins presented outstanding elements, such as low drainage and hydrographic density, increase in the maintenance coefficient, among other distinguishing elements. Therefore, this study will enable it to be a discussion point for other works that want to go into areas whose characteristics intertwine the karstic and terrigenous systems.